2016
DOI: 10.1210/jc.2016-1506
|View full text |Cite
|
Sign up to set email alerts
|

Low Thyroid Hormone in Early Pregnancy Is Associated With an Increased Risk of Gestational Diabetes Mellitus

Abstract: Low thyroid hormone levels in early pregnancy are a risk factor for GDM incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
74
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 40 publications
9
74
3
4
Order By: Relevance
“…Similar findings have been described by Tudela et al . and more recently by Yang et al., who showed this association between GDM and FT4. Whether this finding indicates that elevated TSH levels may contribute to increased insulin resistance and thereby to the development of GDM has yet to be determined.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been described by Tudela et al . and more recently by Yang et al., who showed this association between GDM and FT4. Whether this finding indicates that elevated TSH levels may contribute to increased insulin resistance and thereby to the development of GDM has yet to be determined.…”
Section: Discussionsupporting
confidence: 92%
“…GDM and Type 2 diabetes have risk factors and pathogenesis in common, so it is reasonable to propose that women with either elevated or lower thyroid hormones levels would be prone to develop GDM. Similarly, there is still a lack of consistency in the relationship between TSH levels and GDM risk . Our results are in line with the study by Chaker et al ., which showed that higher TSH and lower free T 4 were related to an increased Type 2 diabetes risk among 8452 participants in the Rotterdam Study .…”
Section: Discussionmentioning
confidence: 91%
“…In‐vitro and in‐vivo experiments have shown that insulin resistance in SCH may be caused by a decrease in peripheral insulin response resulting from excessive glucose–fatty acid cycling, which impairs the ability of insulin to increase blood flow rate to insulin‐sensitive tissues . Although a large‐sample retrospective study conducted by Yang et al . implied no predictive ability of maternal TSH and TPO‐Ab on GDM risk, it is theoretically reasonable that insulin resistance produced by pregnancy‐specific pathological changes and SCH predispose an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 99%